Analysis of Analytically Unsolved Electromagnetic Problems Based on Validated Simulation Models - Parlar, Selin (IEEE, 2007)
Electromagnetic problems are widely investigated with simulation models using computational methods. If validated these models provide an opportunity to analyze more complicated and analytically unsolved problem structures. In this paper, the concept of simulation is dealt from the aspects of simulation types and steps. As a sample problem, even-mode potential and field distribution and transmission characteristics of a one-layer coupled microstrip line are obtained employing a simulation model based on Finite Difference Method. The model is validated by comparing the results yielded by analytical equations. Finally, an arbitrary two-layer coupled microstrip line is analyzed through this verified model without any need for analytical solution emphasizing the benefit of computer as a tool.